Inovação tecnológica e universidades : novas possibilidades da função social da propriedade intelectual em uma sociedade pós-industrial - Bento, Michele Vollrath (2015)
This work is part of the Efficiency and Effectiveness research line of the Constitution and Fundamental Rights in the public law and private law, whose area of concentration lies in Constitutional Law Fundamentals of Public and Private Law, under the Program of Post- law degree (Masters and PhD) at the Catholic University of Rio Grande do Sul - PUCRS. Aims to demonstrate that the institute of intellectual property, through technological innovations, seeking the effective implementation of the principle of the social function provided for in the Federal Constitution as well as the consecration of the same post-industrial society. It is exploratory bibliographic research, theoretical and qualitative, with systemic approach method. As a result, it may be noted that the technological innovations developed within the universities, based on the principle of social function seek to meet the social interests of the community, referring to the principle of human dignity, as a form of consecration of fundamental rights in the State social and democratic rights.